Pengaruh Pengetahuan Investasi, Motivasi Investasi Dan Literasi Keuangan Terhadap Minat Investasi Crypto Pada Gen Z Di Jakarta - Damar Panji Arsyi (Peneliti.net, 2026)
The development of digital investment, particularly crypto assets, has attracted the attention of Generation Z as a group familiar with technology and characterized by adaptability to financial innovation. However, high investment interest needs to be supported by investment knowledge, investment motivation, and financial literacy so that investment decisions are made more rationally and responsibly. This study aims to analyze the influence of investment knowledge, investment motivation, and financial literacy on investment interest among Generation Z in Jakarta. This study uses a quantitative approach with a survey method by distributing questionnaires to 120 Generation Z respondents in Jakarta selected using a purposive sampling technique. Data processing was carried out using IBM SPSS Statistics 27 through data quality testing, classical assumption testing, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R²). The results show that investment knowledge has a positive and significant effect on investment interest with a calculated t-value of 8.171 and a significance level of 0.000. Investment motivation also has a positive and significant effect on investment interest with a calculated t-value of 6.494 and a significance level of 0.000. Furthermore, financial literacy has a positive and significant effect on investment interest with a calculated t value of 6.648 and a significance of 0.000. Simultaneously, investment knowledge, investment motivation, and financial literacy have a positive and significant effect on investment interest with a calculated F value of 192.091 and a significance of 0.000. The Adjusted R Square value of 0.828 indicates that 82.8% of the variation in investment interest can be explained by the three independent variables, while the remaining 17.2% is influenced by other factors outside the research model.